Models and mechanisms of post-stroke dementia and cognitive impairment - Khan, Romeesa; Devlin, Patrick; Urayama, Akihiko; Ritzel, Rodney M. (Frontiers in Stroke, 2025)
Stroke is a leading cause of death and disability globally, with significant long-term impacts such as post-stroke cognitive impairment (PSCI). PSCI affects up to one-third of stroke survivors, substantially increasing their risk of dementia, especially after recurrent strokes. Despite advances in acute stroke treatments, the mechanisms underlying PSCI remain poorly understood. Emerging evidence highlights that PSCI arises from a complex interplay of vascular damage, neurodegenerative pathologies, and chronic inflammation. This review explores the epidemiology and clinical characteristics of PSCI, emphasizing the role of age, education, vascular integrity, and comorbidities such as diabetes. Additionally, we examine experimental findings that utilize rodent models to elucidate the time course and biological mechanisms of PSCI. Notable contributions include insights from transgenic Alzheimer's disease (AD) mouse models, revealing how vascular and amyloid pathologies accelerate cognitive decline post-stroke. Moreover, studies on neuroinflammation and immune responses, such as those involving TREM2, underscore the significance of inflammatory pathways in PSCI. By integrating clinical and experimental findings, this literature review provides a comprehensive understanding of PSCI mechanisms, offering a foundation for developing targeted diagnostic tools and therapeutic interventions to mitigate the long-term cognitive effects of stroke.